Bilateral Radical Nephrectomy & Adrenalectomy – a Rare Case Report - MA, Rakib; HR, Harun; MS, Islam; SM, Waheed; A, Chowdhury (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.166-167